Relationship among Room Head's Leadership Style and Work Motivation with Nurses' Performance in Inpatient Room at AN-NISA Hospital Tangerang - Alpan Alpan; Nining Sriningsih; Ummi Giyanti (Jurnal Ilmiah Keperawatan Indonesia [JIKI], 2019)
In the hospital, nursing staff are the greatest number of hospital human resource and the longest staff who interact with clients. Nursing practice standards,  include  the  standard  of  care  and  the  professional  performance standard that are use as evaluations in assessment nursing care who carry out by nurses. Performance or work performance comes from job performance word (work performance or real achievement someone has ever achieved). The factors that can affect on someone performance, are individual factors: abilities, skills, family background, work experience, social level and demography factor; psychological factors: perception, role, attitude, personality, motivation, and job satisfaction; organizational factors: organizational structure, job design, and leadership. To getting nurses with good performance, hospital need a leader who can understand the nurses' necessary and can provides good environmental assistance to make nurses feel motivated. This study aims to determine the relationship between room head's leaderschip style and work motivation in the inpatient room of AN-NISA Hospital, Tangerang. The research design used is a quantitative correlation with a cross-sectional approach. The sample in this study is  organizer nurses in the inpatient room of AN-NISA Hospital in Tangerang and using  purposive  sampling  technique  with  83  respondents.  Analysis  technique using Chi-square test. The results showed that the dominant style of leadership in inpatient  room  of  AN-NISA  Hospital  Tangerang  is  democratic  style  (48.2%). There is a relationship between the room head's leadership style and the performance of nurses (p.value = 0.033) and there is a relationship between work motivation  and  nurse  performance  (p.  Value  =  0.019).  It  is  hoped  that  this research can be used as a material for evaluating hospitals regarding the leadership style of the head of the room, work motivation and performance of the nurse nurses to be able to maintain and improve the performance of nurses.